Category of number and words, wich express of plurality in the Kazakh and Turkish languages (Journal of Oriental Studies, 2016)
In this article, in a functional and comparative aspect considered words, wich express of plurality in the Kazakh and Turkish languages. Reveals typological peculiarity of category of number in particular forms of multiplicity in the form or two related languages.